PM2.5 promotes replication of VSV by ubiquitination degradation of phospho-IRF3 in A549 cells. (February 2020) - Wu, Jing; Zhu, Kehui; Luo, Xiaolu; Han, Yajing; Zhang, Baohuan; Wang, Zichen; Dong, Shirui; Zou, Xiaoqian; Chen, Xiaojing; Liu, Hongxuan; Wu, Tianyuan; Zheng, Zhong; et al.
Abstract: Both PM2.5 and respiratory viruses are part of the atmospheric constituents. Respiratory viruses are often associated with PM2.5 exposure, but the mechanism of toxicity remains to be explored. The vitro models that adequately reproduce healthy cells or diseased cells exposing to PM2.5 and infecting VSV can provide a useful tool for studying innate immune mechanisms and investigating new therapeutic focus. In the environment of PM2.5, an infection model in which VSV infected A549 cells was established, that mimics the state in which the antiviral innate immune pathways are activated after the respiratory system is infected with RNA viruses. Subsequently, the model was exposed to PM2.5 for 24 h. PM2.5 could be ingested by A549 cells and synergize with VSV to inhibit cell viability and promote apoptosis. The expression of VSV-G were more abundant after VSV-infected A549 cells were exposed to PM2.5 . Furthermore, PM2.5 inhibits VSV-induced IFN-β expression in A549 cells. ISG15, CCL-5, and CXCL-10 had the same expression tendency with IFN-β mRNA, consistently. Interestingly, when MG132 was applied, the expression of p-IRF-3 and IFN-β proteins reduced by PM2.5 were refreshed. Conversely, the expression of VSV-G proteins were decreased. PM2.5 could degrade p-IRF-3 proteins by ubiquitination pathway to inhibit VSV-induced IFN-β expression in A549 cells. Therefore, replication of the VSV viruses was promoted. Highlights: PM2.5 and VSV have a synergistic toxic effect to inhibit cell viability and promote cell apoptosis. PM2.5 can promote the proliferation of VSV in A549 cells. 3.PM2.5 can inhibit the expression of IFN-β, ISG15, CCL-5 and CXCL-10. Degradation of p-IRF-3 by ubiquitination of PM2.5 may be associated with inhibition of VSV-induced IFN-β in A549.